Toxoplasmosis: risk factors in the goat flocks of Argentina´s Northwest region (Veterinary Science, 2021)
A cross-sectional survey was performed in 54 family farm units (FU) and 5 dairy commercial farm (CF) from different regions of Jujuy and Salta provinces, with the aim of studying the association between the seroprevalence against Toxoplama gondii antibodies in goats flocks and risk factors related to the farm units and the goats management. Sera were processed by the indirect fluorescent antibody test IFAT (n = 629) and indirect ELISA (n = 619) techniques. The Chi-square, Odds Ratio (OR) and logistic regression were used for the statistical analysis of the variables. Of the 59 visited flocks, 67.8% of them had at leastone seropositive goat, showing differences between FU (66.7%) and CF (80%). The general prevalence was 18.2% (95 % CI: 15.9-20.6%). The risk factors significantly associated to T. gondii prevalence greater than 20% of the sampled goats would be a percentage of cats greater than 1.1% in relation to the total number of mating goats (OR 5.26; 95% CI: 1.62-17.1) and the milking practice (OR 13.03; 95% CI: 2.19- 80.3). The present results show that infestations by T. gondii in the goat flocks of Salta and Jujuy are important and deserves further studies.flocks of Salta and Jujuy are important and deserves further studies.
Keywords: Toxoplasma gondii, seroprevalence, risk factors, Argentina´s Northwest